Forced degradation of Romprogestin 1 % for HPLC-method development and drug stability assessment - Mădălina Enciu; Viorica Chiurciu; Elena Gabriela Oltean; Adrian G. Nica (Medicamentul Veterinar, 2018)
Forced degradation is an analytical technique applied to a drug product in order to simulate conditions more severe than those in accelerated stability studies. Active substances may suffer degradation during storage over drugs shelf-life; degradation products and degradation pathways should be elucidated to demonstrate the stability of the medicinal product. The oily injection of progesterone is used to synchronize oestrus in ruminants or to treat various clinical manifestations in dogs and cats. Degradation of drug substances between 5 % and 20 % has been accepted as reasonable for validation of chromatographic assays. The chemical methods used for forced degradation of Romprogestin 1 %. injectable solution were: acid hydrolysis, basic hydrolysis and oxidation; the physical method used was the influence of temperature increase. Some parameters were evaluated for validation of the HPLC method (specificity, linearity, detection limit, etc.).